2011
DOI: 10.1161/atvbaha.110.221804
|View full text |Cite|
|
Sign up to set email alerts
|

Early Inflammatory Reactions in Atherosclerosis Are Induced by Proline-Rich Tyrosine Kinase/Reactive Oxygen Species–Mediated Release of Tumor Necrosis Factor-α and Subsequent Activation of the p21 Cip1 /Ets-1/p300 System

Abstract: Objective-Reactive oxygen species (ROS) are involved in the initial process of atherosclerosis, whereas it remains to be determined how atherogenic stimulus causes ROS-mediated proinflammatory reactions. Here, we focused on proline-rich tyrosine kinase (PYK2)-mediated ROS generation and examined how atherogenic stimulus causes early proinflammatory reactions. Methods and Results-PYK2-deficient (knockout [KO]) (PYK2-KO) mice were crossbred with apolipoprotein E (ApoE)-deficient (PYK2-KO/ApoE-KO) mice. PYK2-KO/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…Recently, we have reported that thrombin stimulates Pyk2, a Ca 2ϩ -dependent proline-rich tyrosine kinase, in mediating human aortic smooth muscle cell (HASMC) migration and proliferation and that the activation of Pyk2 is essential for balloon injury-induced neointima formation (17). A role for Pyk2 in atherosclerosis has also been reported previously (18). Because thrombin is produced at the site of vascular injury (6,7) and it causes endothelial cell barrier disruption (19) and inflammation (20), we asked the question of whether it also influences the migration of monocytes/macrophages and, if so, whether it requires Pyk2 activation.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Recently, we have reported that thrombin stimulates Pyk2, a Ca 2ϩ -dependent proline-rich tyrosine kinase, in mediating human aortic smooth muscle cell (HASMC) migration and proliferation and that the activation of Pyk2 is essential for balloon injury-induced neointima formation (17). A role for Pyk2 in atherosclerosis has also been reported previously (18). Because thrombin is produced at the site of vascular injury (6,7) and it causes endothelial cell barrier disruption (19) and inflammation (20), we asked the question of whether it also influences the migration of monocytes/macrophages and, if so, whether it requires Pyk2 activation.…”
supporting
confidence: 56%
“…Previously, we have also shown that Pyk2 plays a role in vascular wall remodeling in response to injury (17). Other studies have reported that Pyk2 is involved in the pathogenesis of atherosclerosis (18). Although our previous study demonstrated that Pyk2-mediated neointimal hyperplasia requires activation of Gab1, p115 RhoGEF, Rac1, RhoA, and Pak1, the mechanisms by which Pyk2 mediates atherosclerosis were not clear.…”
Section: Discussionmentioning
confidence: 76%
“…7B and 7C). It has been reported that p21 is involved in the enhancement of MCP-1 and VCAM-1 expression, which is induced in vascular endothelial cells by TNF- 16) , and the results of experiments that crossed apoE-KO mice with p21-KO mice also suggest that p21 is a proatherogenic molecule 31) . Our study also demonstrated that p21 knockdown significantly suppressed the increase in MCP-1 and ICAM-1 expressions induced by PA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of cyclin-dependent kinase inhibitor p21Cip1 was, in part, dependent on PYK2 and associated JNK signaling and acted as a co-activator for VCAM-1 and MCP-1 transcription in endothelial cells (890). Macrophage apoptosis was increased while macrophages showed less inflammation and greater efferocytosis capability with p21Cip1 KO.…”
Section: %mentioning
confidence: 95%
“…Additionally, the PYK2-Src complex can apparently activate ADAM17 with release of HB-EGF and transactivation of EGFR signaling, providing an additional source of PI3K and Grb2-Sos-Ras activation (616,617) and a sustained release of ROS (805). Other binding partners of PYK2 are Vav1 (in leukocytes) (586) and Vav2 (in endothelium) (890). Vav is the sixth letter of the Hebrew alphabet and was chosen as the name for Vav1 since it was the sixth oncogene identified in the laboratory of its Jewish discoverer.…”
Section: Inflammatory Signaling Through At1r Is Largely Mediated By Pyk2mentioning
confidence: 99%